MODEL PENGELOLAAN KELAS INKLUSI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2021)
Inclusive class is a class that managed to serve learners with diverse characteristics, normal children and children with disabilities.This study aims to analyze the characteristics of students with special needs who study in SDN Sumbersari 1 Malang and SDN Junrejo 01 Batu, and to analyze the strategy of inclusive class management and the implication of inclusive classroom management modelon the success of Islamic Education Learning in the inclusive classroom SDN Sumbersari 1 Malang and SDN Junrejo 01 Batu.This study used a qualitative approach case study type with multi-site design. The findings showed that: 1) Characteristics graders inclusion in the SDN are: a) Students who are normal and b) Students with disabilities, consists of autism, mental retardation, ADHD, physical impairment, dyslexia, emotional disturbances and slow learner. 2) Based on the characteristics students, the inclusive classroom management model applied in the second SDN is a model of regular classes and special classes full models. But for SDN Sumbersari 1 Malang regular class models using pull put. The strategies GPAI manage regular classroom is the method of direct instruction in the classical and the provision of duty is differentiation according to the students' abilities. While the full special classroom management strategies conducted by GPK with the delivery of content and administration tasks that are specific to ABK. In addition to providing GPK from school, parents also play a role in the provision of shadow (companion) for students ABK in schools so that learning is effective, and 3) Implications of the inclusive classroom management model have a positive impact on learning outcomes, in addition students are also accustomed to apply Islamic religion values in real life, able to adapt, communicate and socialize well to each other.